Analisis Debit Banjir Rancangan dengan Data Curah Hujan di DAS Waru Kabupaten Banggai - V.W. Andiese; S.R. Oktavia; N.B. Rustiati; T. Amaliyah; N. Djupanda (Civil Engineering Department, Tadulako University, 2022)
The meteorological data is important to design and planning the water resources system and irrigation. The complete and long of data is needed to make sure the accuracy of the water avaibility. Unfortunately, the avaibility of the rainfall data is not always complete. So it’s needed the methods to fill the lacking rainfall data. The location of the research is Waru watershed at the Banggai Regency, Central Sulawesi. The cause of repeated flooding in 2019 and 2020 was the disability of the watershed to accommodate higher rainfall intensity. The goals of the research was to compare the design flood discharge values obtained, using the lacking of rainfall data and rainfall data that had been filled in. In filling in the missing rainfall data, 2 methods are used, that are the Algebraic Average method and the Inverse Square Distance method. Then the calculation continues with the design flood discharge, using the Rational method. The final result is the design flood discharge values from the two rainfall data with different conditions will be compared to see the difference between the both of the methods. The value of the difference in design flood discharge obtained from this comparison is 0.0552 m³/s for a 2 year return period, 37.0313 m³/s for a 5 year return period, 79.3389 m³/s for a 10 year return period, 163.1544 m³/s for a 25 year return period, 255.1732 m³/s for the 50-year return period and 380.8701 m³/s for the 100-year return period.